Numerical modeling of the tide in the coast ar-ea Casablanca-Mohammedia (Morocco) - Mouakkir, Laila; Mordane, Soumia (International Journal of Advanced Geosciences, 2017)
The objective of this study is to simulate the tidal circulation in the coastal area Casablanca-Mohammedia located on the Moroccan Atlantic. Simulations of the tidal currents of this zone use the 2D version of the MECCA (Model for Estuarine and Coastal Circulation Assessment). These simulations are based on the depth-integrated dynamical equations of turbulent motion. Equations are solved by using the implicit finite-differences techniques. The modelincorporates the actual bottom topography and the effects of the Earth rotation. As forcing mechanism, the model uses the tidal heights prescribed along the open boundaries.As first results, numerical experiments show that the model provides good results compared to those of the altymetric model TPXO.